(untitled) (Revista de História Regional, 2007)
Theoretical and Methodological paremeters in the New Cultural History have enabled the analysis of reading habits and representations as elements responsible dor the appearance of a religious movement which began in the North of Paraná state. This movement took over a messianic-millenarian profile. The performance of a charismatic leader and the belief of his followers in miraculous cures and apocalyptical redemption made that an intense process of adaptation of cultural elements started to happen. This occured in the midst of aggravated social conditions. These elements have been woven throughout a long duration period and got new meanings which defined behaviour orientation and established an identity construction of those that adhered to the practices mentioned. The strength and solidity of the representations formed by the imaginary have reached its peak when it was announed and expected that, in the year of 1999, Jesus Christ would come again with the purpose to establish a new idyllic millenarian kingdom on earth.